Whole-Body Muscle MRI in Patients with Hyperkalemic Periodic Paralysis Carrying the SCN4A Mutation T704M: Evidence for Chronic Progressive Myopathy with Selective Muscle Involvement - Lee, Young Han; Lee, Hyung-Soo; Lee, Hyo Eun; Hahn, Seok; Nam, Tai-Seung; Shin, Ha Young; Choi, Young-Chul; Kim, Seung Min (Journal of clinical neurology (Seoul, Korea), 2015)
Hyperkalemic periodic paralysis (hyperKPP) is a muscle sodium-ion channelopathy characterized by recurrent paralytic attacks. A proportion of affected individuals develop fixed or chronic progressive weakness that results in significant disability. However, little is known about the pathology of hyperKPP-induced fixed weakness, including the pattern of muscle involvement. The aim of this study was to characterize the patterns of muscle involvement in hyperKPP by whole-body magnetic resonance imaging (MRI). We performed whole-body muscle MRI in seven hyperKPP patients carrying the T704M mutation in the SCN4A skeletal sodium-channel gene. Muscle fat infiltration, suggestive of chronic progressive myopathy, was analyzed qualitatively using a grading system and was quantified by the two-point Dixon technique. Whole-body muscle MRI analysis revealed muscle atrophy and fatty infiltration in hyperKPP patients, especially in older individuals. Muscle involvement followed a selective pattern, primarily affecting the posterior compartment of the lower leg and anterior thigh muscles. The muscle fat fraction increased with patient age in the anterior thigh (r=0.669, p=0.009), in the deep posterior compartment of the lower leg (r=0.617, p=0.019), and in the superficial posterior compartment of the lower leg (r=0.777, p=0.001). Our whole-body muscle MRI findings provide evidence for chronic progressive myopathy in hyperKPP patients. The reported data suggest that a selective pattern of muscle involvement-affecting the posterior compartment of the lower leg and the anterior thigh-is characteristic of chronic progressive myopathy in hyperKPP.